Inflammation and Oral Contraceptive Use in Female Athletes Before the Rio Olympic Games - Larsen, Brianna; Cox, Amanda; Colbey, Candice; Drew, Michael; McGuire, Helen; Fazekas de St Groth, Barbara; Hughes, David; Vlahovich, Nicole; Waddington, Gordon; Burke, Louise; Lundy, Bronwen; West, Nicholas; et al. (Frontiers in Physiology, 2020)
Purpose: To investigate the association between synthetic ovarian hormone use (i.e., the oral contraceptive (OC) pill) and basal C-reactive protein (CRP), peripheral blood immune cell subsets, and circulating pro- and anti-inflammatory cytokine concentrations in elite female athletes. Methods: Elite female athletes (n = 53) selected in Rio Summer Olympic squads participated in this study; 25 were taking an OC (AthletesOC) and 28 were naturally hormonally cycling (AthletesNC). Venous blood samples were collected at rest for the determination of sex hormones, cortisol, CRP, peripheral blood mononuclear memory and naïve CD4+ T-cells, CD8+ T-cells and natural killer cells, as well as pro- and anti-inflammatory cytokine concentrations. Results: C-reactive protein concentrations were elevated (p < 0.001) in AthletesOC (median = 2.02, IQR = 3.15) compared to AthletesNC (median = 0.57, IQR = 1.07). No differences were reported for cortisol, cytokines, or PBMC immune cell subsets, although there was a trend (p = 0.062) for higher IL-6 concentrations in AthletesNC. Conclusion: Female Olympians had substantially higher CRP concentrations, a marker of inflammation and tissue damage, before the Rio Olympic Games if they used an OC. Future research should examine the potential consequences for athlete performance/recovery so that, if necessary, practitioners can implement prevention programs.